Fc engineered ACE2-Fc is a potent multifunctional agent targeting SARS-CoV2 - Wines, Bruce D.; Kurtovic, Liriye; Trist, Halina M.; Esparon, Sandra; Lopez, Ester; Chappin, Klasina; Chan, Li-Jin; Mordant, Francesca L.; Lee, Wen Shi; Gherardin, Nicholas A.; Patel, Sheila K.; Hartley, Gemma E.; et al. (Frontiers in Immunology, 2022)
Joining a function-enhanced Fc-portion of human IgG to the SARS-CoV-2 entry receptor ACE2 produces an antiviral decoy with strain transcending virus neutralizing activity. SARS-CoV-2 neutralization and Fc-effector functions of ACE2-Fc decoy proteins, formatted with or without the ACE2 collectrin domain, were optimized by Fc-modification. The different Fc-modifications resulted in distinct effects on neutralization and effector functions. H429Y, a point mutation outside the binding sites for FcγRs or complement caused non-covalent oligomerization of the ACE2-Fc decoy proteins, abrogated FcγR interaction and enhanced SARS-CoV-2 neutralization. Another Fc mutation, H429F did not improve virus neutralization but resulted in increased C5b-C9 fixation and transformed ACE2-Fc to a potent mediator of complement-dependent cytotoxicity (CDC) against SARS-CoV-2 spike (S) expressing cells. Furthermore, modification of the Fc-glycan enhanced cell activation via FcγRIIIa. These different immune profiles demonstrate the capacity of Fc-based agents to be engineered to optimize different mechanisms of protection for SARS-CoV-2 and potentially other viral pathogens.